2021
DOI: 10.1371/journal.pone.0252823
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus velezensis strain MBY2, a potential agent for the management of crown gall disease

Abstract: The reduction of the use chemical pesticides in agriculture is gaining importance as an objective of decision-makers in both politics and economics. Consequently, the development of technically efficient and economically affordable alternatives as, e.g., biological control agents or practices is highly solicited. Crown gall disease of dicotyledonous plants is caused by ubiquitous soil borne pathogenic bacteria of the Agrobacterium tumefaciens species complex, that comprises the species Agrobacterium fabrum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…For instance, Chen et al [ 28 ] reported that B . velezensis LM2303 had strong antagonist activity against Fusarium head blight; the study of Ben Gharsa et al [ 29 ] describes that B . velezensis strain MBY2 can be used as a biological agent for crown gall disease management; Chen et al [ 30 ] reported that B .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Chen et al [ 28 ] reported that B . velezensis LM2303 had strong antagonist activity against Fusarium head blight; the study of Ben Gharsa et al [ 29 ] describes that B . velezensis strain MBY2 can be used as a biological agent for crown gall disease management; Chen et al [ 30 ] reported that B .…”
Section: Discussionmentioning
confidence: 99%
“…PCR amplification of marker genes was performed using OnePCR ™ Ultra Supermix with Fluorescent Dye (Bio-Helix) according to the methodology described by Ben Gharsa et al (2021) with some modifications. The primer pairs used for the 16S rRNA , gyrA , and groEL genes are detailed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was extracted using a DNA Miniprep Kit (ZymoBIOMICS, California, USA) following the manufacturer’s instructions. The primer combination for the three markers was as follows: for 16S, GM3F (5′-AGAGTTTGATCMTGGC-3′) and GM4R (5′-TACCTTGTTACGACTT-3′) [ 29 ]; for gyr A, 42f (5′-CAGTCAGGAAATGCGTACGTCCTT-3′) and 1066 (5′-CAAGGTAATGCTCCAGGCATTGCT-3′) [ 30 ]; and for rpoB, 2292f (5′-GACGTGGGATGGCTACAACT-3′) and 3354r (5′-ATTGTCGCCTTTAACGATGG-3′) [ 31 ]. Each marker was amplified using polymerase chain reaction (PCR) with MasterMix (Promega, Madison, WI, USA) in the following reaction mixture: 10 ng of DNA and 0.25–0.5 pmol of the forward and reverse primers in a total volume of 10 μL.…”
Section: Methodsmentioning
confidence: 99%